2021
DOI: 10.15586/aei.v49i5.465
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularis induces surface high expression of inhibitory killer immunoglobulin‐like receptor on natural killer cells

Abstract: Alveolar echinococcosis (AE) is a malignant and fatal parasitic disease caused by the larvae of Echinococcus multilocularis (E. multilocularis), which inhibits the activity and proliferation of natural killer (NK) cells. In this study, the functional alteration of hepatic NK cells and their related molecules were studied. The AE-infected patient’s tissue was fixed with formalin, embedded in paraffin, and stained with Masson’s trichrome or hematoxylin and eosin (H&E). Single cells from AE-infected patient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Epitopes on the protein sequence may be destroyed during processing to reduce IgE-binding capacity, and new epitopes can be created to improve IgE-binding capability. Consequently, it is essential to assess the impact of processing on the allergenicity of egg proteins [ 265 , 266 ].…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%
“…Epitopes on the protein sequence may be destroyed during processing to reduce IgE-binding capacity, and new epitopes can be created to improve IgE-binding capability. Consequently, it is essential to assess the impact of processing on the allergenicity of egg proteins [ 265 , 266 ].…”
Section: Allergenicity From Egg Proteinsmentioning
confidence: 99%
“…Factors such as pathogenic infection (e.g., infection of Echinococcus multilocularis), liver metabolic disorder (e.g., NAFLD), and tumor development can induce NK cell dysfunction, leading to liver fibrosis [11,84,85]. Some treatments have been shown to regulate NK cell function to inhibit liver fibrosis, such as alcohol dehydrogenase 3 (ADH3) inhibitors, mi-croRNAs, NKG2D activators, and natural products.…”
Section: Treatments Improve the Cytolytic Function Of Nk Cells To Hscsmentioning
confidence: 99%
“…The regulatory network of immune cells in the liver plays a vital role in maintaining tissue integrity and defending against infection. The E. multilocularis infection process stimulates both adaptive and innate immune responses in the host, where macrophages (7), NK cells (8), and T cells (9) regulate the immune response through different mechanisms for host defense (10). It has been shown that treatment based on immune checkpoints PD-1 (11), PD-L1 (12), and TIGIT (13,14) immunotherapy has potential for the treatment of AE disease but is still not practiced in the clinic.…”
Section: Introductionmentioning
confidence: 99%